The Role of Influencers and Source Credibility in Influencing Purchase Intention for Wardah Products - Muhammad Falhan Juliadi; Aang Curatman (Universitas KH. Abdul Chalim Mojokerto, 2026)
The beauty industry in Indonesia is experiencing rapid growth in line with the increasing use of social media and the role of influencers in digital marketing. Wardah, as a leading halal cosmetics brand, utilizes influencer marketing strategies to shape consumer purchasing interests. This study aims to analyze the influence of influencers and source credibility on the purchase intention of Wardah products in Indonesia, both partially and simultaneously. This study uses a quantitative approach with an associative method. Data were collected through an online questionnaire of 130 respondents who had seen Wardah promotional content from influencers on social media. Data analysis techniques used multiple linear regression with the help of the SPSS program. The results showed that influencers had a positive and significant effect on purchase intention, as did source credibility. In addition, influencers and source credibility simultaneously also have a significant effect on the purchase intention of Wardah products. These findings confirm the relevance of the Theory of Planned Behavior in explaining the formation of consumer purchase intentions in the context of influencer marketing. This study is expected to contribute theoretically to digital marketing studies and provide practical implications for companies in designing effective and credibility-based influencer marketing strategies.